SPEAK UP USING CARD GAMES - Prihatin, Yoga (CERMIN, 2010)
Abstract: This article discusses the use of card games in speaking class ofspoken descriptive text (describing thing, place, and person). There aretwo kinds of card games, twenty question game, and Stick a Card-WordGuessing Game. The techniques used are role-play, and discussion. Cardgames are one of useful techniques that are encouraging and motivatingstudents in learning and developing speaking skill. It creates meaningfulcontext of learning English in natural ways.